2012
DOI: 10.1016/j.ejvs.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The Removal of Post-sclerotherapy Pigmentation following Sclerotherapy Alone or in Combination with Crossectomy

Abstract: IPL + RF therapy is effective for eliminating permanent skin hyperpigmentation after sclerotherapy. US is also useful in this therapeutic method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In turn, modern Duplex ultrasound devices allow excellent morphological evaluation of both the CL and SCL, by using the same probes dedicated to routine vascular investigations. 7,8…”
Section: Introductionmentioning
confidence: 99%
“…In turn, modern Duplex ultrasound devices allow excellent morphological evaluation of both the CL and SCL, by using the same probes dedicated to routine vascular investigations. 7,8…”
Section: Introductionmentioning
confidence: 99%
“…23 Our findings indicate that patient satisfaction increased even among those presenting a hyperpigmentation complication. 24 Following up individuals for a long period may lead to a better understanding of patient-related outcomes, since the recurrence of varicose veins and adverse effects may appear after several months. During this period, the photographic documentation of patient evolution is essential in assessing skin changes.…”
Section: Discussionmentioning
confidence: 99%
“…6,26,33 Our recent study of skin hyperpigmentation following sclerotherapy showed that IPL reduced or even resolved hyperpigmented lesions. 34,35 Based on that, we used IPL in 4 patients after endovenous thermal ablation with success. However, it is difficult to recommend the method based on such scant experience.…”
Section: Discussionmentioning
confidence: 99%